Scientific Mapping of Organizational Resilience Research: Evidence from Global Publications - Loso Judijanto (Jurnal Multidisiplin West Science, 2026)
The paper under discussion offers a scientometric map of organizational resilience studies, conducted through an extensive review of all the existing academic literature on the subject matter across the globe. Organizational resilience is defined as the capacity of organizations to foresee, adjust to, cope with, and recover from unfavorable conditions while fulfilling their fundamental tasks. As a result of increased interest from the part of scholars to explore this phenomenon, organizational resilience has become a significant area of academic inquiry in recent years. Bibliometrics was used as the methodology for conducting this research. The author employed bibliometric analysis techniques that included coauthorship, cocitation, and keyword co-occurrence to construct the intellectual structure of this scientific discipline, identify its most prominent themes, and trace its development through time. It should be emphasized that organizational resilience became increasingly interdisciplinary during the period under consideration. For instance, themes such as crisis management, digital transformation, and sustainability became popular within the context of organizational resilience studies. However, more traditional managerial practices, including human resource and knowledge management, continue to be relevant when it comes to organizational resilience.